Graphical user interface (GUI) development for energy saving control system - Nur Munirah, Mohd Din (2008)
Graphical User Interface development for energy saving air-conditioning control system means we can control the air-conditioning system by using software to reduce electricity cost. This system will assured us to reduce energy wasting in the lecture halls before and after the lecture time. During the lectures time, most of user forget or in rushing to switch off/on the lighting system and air-conditioner and at the same time we already wasting the energy. So this programme will develop to help us to conduct the switch of lighting system and air-conditioner by clicking just from the computer/PC.User can control the air-conditioning by using their laptop or personal computer (PC). This software is very user friendly. The software is connected to the lighting and air-conditioning system by a circuit consist PIC 18F4620, relay interface circuit and RS232 communication module. The circuit connected to the PC using serial communication port (comm1).